Development of 'Sifir Run' Mathematical Mobile Game for Learning Multiplication Topics in Primary School Students - Mohd Ishak, Amira; Abdul Rahman, Mohd Hishamuddin (Journal of Engineering, Technology, and Applied Science (JETAS), 2021)
Bidang permainan mudah alih pada era ini telah melonjakkan evolusi pendidikan dan juga membangunkan kemahiran kognitif, spatial dan kemahiran motor (skill) serta meningkatkan kemahiran ICT. Pembangunan ICT dan teknologi telah memberi banyak peluang dan ruang untuk diterokai dalam bidang permainan mudah alih. Sifir Run merupakan sebuah aplikasi permainan mudah alih yang bertemakan pembelajaran sifir. Pembangunan aplikasi ini bertujuan untuk meningkatkan kemahiran menghafal sifir dalam kalangan murid sekolah rendah. Objektif projek ini adalah untuk mengenalpasti permasalahan murid dalam operasi darab, mereka bentuk dan membangunkan permainan mudah alih yang bertemakan sifir dan mengkaji kebolehgunaan aplikasi permainan mudah alih tersebut. Pembangunan aplikasi ini dijalankan dengan menggunakan model ADDIE. Terdapat seramai 20 orang responden dipilih oleh pengkaji bagI menjalani fasa penilaian untuk menguji kebolehgunaan aplikasi permainan mudah alih Sifir Run. Development of 'Sifir Run' Mathematical Mobile Game for Learning Multiplication Topics in Primary School Students Abstract: The field of mobile games in this era has accelerated the evolution of education and also developed cognitive, spatial and motor skills (skills) as well as improve ICT skills. The development of ICT and technology has provided many opportunities and spaces to be explored in the field of mobile gaming. Sifir Run is a mobile game application themed on learning ciphers. The development of this application aims to improve the skills of memorizing ciphers among primary school students. The objective of this project is to identify students' problems in multiplication operations, design and develop cipher -themed mobile games and study the usability of such mobile game applications. The development of this application was carried out using the ADDIE model. A total of 20 respondents were selected by the researcher to undergo the evaluation phase to test the usability of the Sifir Run mobile game application. Keywords: Educational Games, Mobile Computer Games, Multiplication.